POLA KOMUNIKASI PADA ACARA RITUAL RUWATAN POTONG RAMBUT GEMBEL DI DIENG WONOSOBO - Wiyanto Hidayatullah (Universitas Tribhuwana Tunggadewi, 2020)
Abstract. Dreadlocks Ruwatan is a hair cutting ceremony for children with dreadlocks (gembel) performed by people in the Dieng Plateau (Dieng Plateau), Central Java. Ruwatan ritual which is held on the first Suro according to the Javanese Calendar aims to clean or free dreadlocks children from sukerta / sesuker (bad luck, sadness, or disaster). The belief that children with dreadlocks are descendants of Kiai Kolodete or entrusted Kanjeng Ratu Kidul (Nyai Roro Kidul) has become amyth hereditaryin the lives of the Dieng people. They also believe that dreads should only be cut if the child in question has the will / asked for it and must be done throughrituals ruwat or ruwatanled by local traditional elders. This sentence can only be done after the parents fulfill the